Exploration of contributing factors leading to a decrease in agricultural productivity in restituted farms of Ehlanzeni District Mpumalanga province - Mahule, Siboshiwe Gertrude (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.